RANCANG BANGUN SISTEM KONTROL PEMOTONG PLAT BESI BERBASIS ARDUINO MEGA 2560 - Jesse Sebastian; Bambang Siswojo; n/a Rahmadwati (Jurnal Mahasiswa TEUB, 2022)
The steel cutting process in the industry is carried out to be consistent as desired. Automation design using Plasma Cutting is one of the mechanisms used by the industry in connecting rods in steel building construction and machine construction, so that the selector is more efficient and reduces the error rate in the selection process. The Steel Cutting design is driven by 2 stepper motors on X axis and 1 stepper motor on Y axis, the welding speed can be adjusted and starts with a straight speed of up to 40cm. In this study, using a lead screw and a ball screw to change the translational motion of a stepper motor with a precision level of 5mm or the equivalent of 200 steps per rotation so that 1 step is 1.8˚, the TB6600 module and Arduino Mega 2560 as a controller are tested on a welding table. measuring 75 cm long x 70 cm wide x 40 cm high and the system design uses a Time Schedule Control type sequential method. Based on the results of experiments and the creation of a system to regulate translational motion, the average error is 1.02%. With a small error of 0.75%, it can be concluded that the tools in the system can be used. Keywords: Plasma Cutting,